Ciri-ciri panggilan katak Borneo (Genus:Hylarana)dari populasi Sarawak,Malaysia Timur - Ramlah Zainuddin,; Mustafa Abdul Rahman,; Badrul Munir Mohd Zain,; Shukor Mohd Nor,; Norhayati Ahmad,; Robert Finger, (Universiti Kebangsaan Malaysia, 2009)
Recordings of Bornean frog calls from the genus Hylarana were conducted at seven study sites in Sarawak, Malaysia. As many as 12 individuals from five species of Bornean frogs were successfully recorded and analysed. From 38 calling parameters, only 27 could explain call characteristics of the Bornean frogs. The size of male frogs influenced the energy of calling significantly between 90:50% of the peak amplitude, frequency of note between 50%, duration of calling to reach half of the frequency modulation, and the rate of repeated note. The size of Bornean frog showed a marginally significant difference in the basic frequency and dominant calls. Additionally, distribution of calling parameters and Euclid dendogram support taxonomic identifications of each of the Bornean frog species studied.